Application of security threat intelligence based on big data analysis in telecom operators - Mingxia BO; Hongyu TANG; Chen MA; Jian ZHANG (Dianxin kexue)
As a powerful tool for operators to deal with means of new attack and ever-changing security threats,threat intelligence is also the core power to transform traditional passive defense into active defense.The importance of threat intelligence to operators was introduced,the productive process of threat intelligence was analyzed in detail,and finally the typical application scenarios of threat intelligence were given,which could provide technical reference for telecom operators in the practice of threat intelligence.